Investigation of the Effect of the COVID-19 Pandemic on Anxiety Levels and Career Satisfaction of Dentistry Students - Kır, Furkan; Bayrak, Ata Batuhan; Büyükgöze-Dindar, Mediha (Journal of Dentistry Indonesia, 2024)
Objective: This study aimed to investigate the effect of the COVID-19 pandemic on the anxiety levels and career satisfaction of dentistry students. Methods: A total of 220 dentistry students were included in the study. A questionnaire was mailed to dentistry students at Trakya University between June 2021 and January 2022. Beck Anxiety Inventory (BAI) was used to evaluate anxiety levels. Data were analyzed, and p < 0.05 was considered statistically significant. Results: The mean BAI scores of the participants were 14.6 ± 13.6. The anxiety levels of the females were significantly higher than the males (p = 0.004). There was a significant relationship between the level of knowledge about COVID-19 and anxiety (p = 0.032). More than half of dentistry students were anxious about the pandemic conditions and concerned about being infected during treatment. Moreover, most participants were anxious about infecting their patients and families, yet 86.8% do not regret choosing dentistry as a profession. Conclusion: An increase was observed in the anxiety levels caused by the pandemic in dentistry students. The outcomes of the current study revealed that the COVID-19 pandemic affected female dental students more. Although the COVID-19 pandemic negatively affected the psychological health of dental students, most participants were satisfied with their careers.